EVALUATION OF PATIENTS WITH CORONARY ARTERY DISEASE FOR MAJOR MODIFIABLE RISK FACTORS FOR ISCHEMIC HEART DISEASE - Zahidullah, Mohammad; Aasim, Muhammad; Khan, Ihsanullah; Muhammadzai, Hamza Z; Shah, Mumtaz Anwar; Ali, Niaz; Mohammad, Amir; Muzahir, Azeem; Rehman, Muhammad (Journal of Ayub Medical College Abbottabad, 2012)
Background: Incidence of cardiovascular diseases is on the rise in developing countries. Deaths due to ischemic heart disease can be reduced by modifying the risk factors. The present study was conducted to evaluate the patients scheduled for Coronary Artery Bypass Surgery for the presence of major modifiable risk factors for ischemic heart disease (IHD). Methods: It was a descriptive study. All patients who underwent elective Coronary Artery Bypass cardiac surgery between November 1, 2008 and February 28, 2009 at Rehman Medical Institute, Peshawar, were included in the study. Presence of Diabetes, Hypertension, Smoking, Dyslipidemia, Sedentary life style, and Obesity was looked for in these patients. Results: A total of 104 patients were studied during this period. Majority (97.11%) of patients had at least one major modifiable risk factor for IHD. Sedentary life style (53.84%) was the most common risk factor present in these patients followed by hypertension and dyslipidemia (47.11% each), smoking (43.27%), diabetes (35.57%), and obesity (9.61%). Multiple risk factors (two or more) were found in 78 (75.0%) of patients. Conclusion: Most of the patients with coronary artery disease, severe enough to warrant coronary artery bypass grafting, have at least one of the major modifiable risk factors for IHD. Modification of these factors may well reduce the disease burden of CAD and reduce the cardiovascular mortality. Keywords: Coronary Artery Bypass Surgery, Ischemic Heart Disease, Major Modifiable Risk Factors, Hypertension, Smoking, Diabetes, Dyslipidemia, Sedentary Life Style, Obesity